ON REPRESENTATION AND POWER: PORTRAIT OF A VODUN LEADER IN PRESENT-DAY BENIN - (:unkn) unknown (My University, 2014)
In this paper, the author discusses the power of vodun leaders in present-day Benin, and more specifically anti-witchcraft cults born from the encounter with world religions. Offering an analysis inspired by Louis Marin’s theory on power in its representation, the author illustrates her analysis through the portrait of a vodun leader with a view to escape from a functionalist analysis of occult power or syncretism. With the baroque mirror metaphor conceived as a device, which underscores what it is that connects heterogeneous practices, Tall describes what is shown in the rituals and practices of a vodun leader and emphasizes the centrality of the transubstantiation phenomenon in the production of a community of believers.
Keywords: African Research